PERLINDUNGAN HUKUM TERHADAP KERUGIAN PADA PELAKU USAHA JASA MAKE UP AKIBAT WANPRESTASI KONSUMEN - Aidila Safitri; Ida Friatna (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
The Developments in the beauty industry are growing rapidly and various beauty trends are emerging as market demand increases. This article aims to examine the legal protection of business actors due to defaults committed by consumers. This type of research is a qualitative descriptive approach through case studies. Primary data was obtained from interviews with a number of makeup artists in Pidie Regency, Indonesia. While secondary data is obtained from a number of articles related to this research. The results show that legal protection of business actors is not going well, especially due to consumers who do not have good faith to pay for orders that have been ordered. For example, in the case experienced by Yolanda make up where she was supposed to get a payment of Rp. 600,000 for the engagement event according to the price list, but only received a payment of Rp. 300,000, meaning that the rest was not paid by the consumer because the reason was not as expected. In this case, normally, consumer protection has been established based on Law No.8 of 1999 concerning Consumer Protection (UUPK), but in law enforcement, disputes like this must be resolved personally by the parties, which often does not get an agreement.